2021
DOI: 10.1186/s12889-021-10929-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the tuberculosis case-finding and prevention cascade among people living with HIV in Zambia – 2018: a cross-sectional cluster survey

Abstract: Background The Ministry of Health Zambia recommends tuberculosis preventive treatment (TPT) with 6 months daily isoniazid for all people living with human immunodeficiency virus (HIV) after ruling out active tuberculosis disease. We sought to estimate the percentage of people living with HIV who progress through each stage of the tuberculosis case-finding and prevention cascade in two provinces with the highest tuberculosis burden in Zambia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Our findings, based on a large cohort of CLHIV aged 1–14 years from western Kenya (a region known for its high TB/HIV prevalence), contribute to the limited literature on IPT initiation and completion among CLHIV from high TB/HIV burden countries. The uptake of IPT among CLHIV in Kenya still falls short of the global target of >90% [ 19 ] and could be lagging behind that in adults living with HIV as reported by studies from other high TB prevalence countries [ 20 , 21 ]. These findings strengthen the evidence from previous Kenyan studies that reported suboptimal IPT initiation among CLHIV, although those studies were conducted in regions of the country with lower TB/HIV prevalence, were based on small sample sizes and did not include all age groups [ 12 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, based on a large cohort of CLHIV aged 1–14 years from western Kenya (a region known for its high TB/HIV prevalence), contribute to the limited literature on IPT initiation and completion among CLHIV from high TB/HIV burden countries. The uptake of IPT among CLHIV in Kenya still falls short of the global target of >90% [ 19 ] and could be lagging behind that in adults living with HIV as reported by studies from other high TB prevalence countries [ 20 , 21 ]. These findings strengthen the evidence from previous Kenyan studies that reported suboptimal IPT initiation among CLHIV, although those studies were conducted in regions of the country with lower TB/HIV prevalence, were based on small sample sizes and did not include all age groups [ 12 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 27 A cross-sectional study from Zambia also found low TPT completion rates with only 38% of the 25% of eligible PLHIV who initiated TPT completing treatment. 28 …”
Section: Challenges That Drive Tb-related Mortality In Plhivmentioning
confidence: 99%
“… 84 Improving the efficiency of healthcare systems and effective training on TPT may also allow for better implementation of TPT and reduced TB mortality in PLHIV. 27 , 28 …”
Section: Potential Solutions To Mitigate Tb-related Mortality In Plhivmentioning
confidence: 99%
See 2 more Smart Citations